The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jgeb.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of chicken feathers for xanthan gum production using Xanthomonas campestris MO-03

Abstract: Xanthan gum is an important commercial polysaccharide produced by Xanthomonas species. In this study, xanthan production was investigated using a local isolate of Xanthomonas campestris MO-03 in medium containing various concentrations of chicken feather peptone (CFP) as an enhancer substrate. CFP was produced with a chemical process and its chemical composition was determined. The addition of CFP (1–8 g/l) increased the conversion of sugar to xanthan gum in comparison with the control medium, which did not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…These results suggested that the increase in xanthan gum concentration was not dependent on the increase in the growth related. Similar results were reported in the previous studies [23][24][25]. The initial nitrogen concentration and type also affected xanthan production.…”
Section: Effect Of Cfp On Xanthan Gum Productionsupporting
confidence: 90%
See 4 more Smart Citations
“…These results suggested that the increase in xanthan gum concentration was not dependent on the increase in the growth related. Similar results were reported in the previous studies [23][24][25]. The initial nitrogen concentration and type also affected xanthan production.…”
Section: Effect Of Cfp On Xanthan Gum Productionsupporting
confidence: 90%
“…Others have reported that some organic nitrogen sources such as yeast extract [29], ram horn peptone [30], and peptone-tyrptone [28] contribute to the formation of xanthan gum. The results of our previous studies [19,21,23] showed that CFP contains all of these amino acids (alanine, cysteine, glutamate, and proline) at varying concentrations. For the production of xanthan gum, X. campestris requires some micro-(e.g., K, Fe, P, Mg, S and Ca salts) and macronutrients (C and N) [31,32].…”
Section: Effect Of Cfp On Xanthan Gum Productionmentioning
confidence: 94%
See 3 more Smart Citations